American education - Spring, Joel H. (McGraw-Hill, 2012)
"Clear, concise, and authoritative compact and affordable, too with scholarship that is often cited as a primary source, American Education brings up-to-date information and challenging perspectives to teacher educators' classrooms. Revised every two years, American Education provides a fresh, concise, and up-to-date introduction to the historical, political, social, and legal foundations of education and to the profession of teaching in the United States"